PRE-POST PEMBERIAN AROMATERAPI BUNGA LAVENDER TERHADAP SKALA ANSIETAS PADA PASIEN PRE-MASTEKTOMI - Eka Ristin Tarigan; Rostime Hermayerni Simanullang; Afnijar Wahyu; Laurena Ginting; Nurhamida Fithri (Jurnal Online Keperawatan Indonesia, 2022)
Background: Breast cancer is group of abnormal cells in the breast that continue to grow multiply. Mastectomy is one of the options for surgical action in breast cancer. In patients who will undergo mastectomy, all breast tissue and axillary lymph nodes are suspected. Surgery will cause psychological disorders in the form of anxiety that can lead to complications during surgery. One way to reduce anxiety is through the provision of aromatherapy, especially aromatherapy lavender, which is known to be sedative. Purpose: the aims to determine the effect of aromatherapy on anxiety scale in pre mastectomy patients. Method: this study was used a quasi-experimental research design with the one group pre- and post-test without control method. Determination of sample size was using purposive sampling teqniuqe with 15 respondents. The instrument to assess anxiety is the Hamilton Anxiety Rating Scale (HARS). Data from the research results were analyzed by statistical tests, namely the Wilcoxon test. Results: this study show that there is a significant effect of pre- and post-administration of aromatherapy of lavender flowers to decrease the level of anxiety in patients with pre-mastectomy with p value (p = 0,001) <0.05. Conclussion: the granting of aromatherapy lavender can reduce of anxiety levels in patients with pre-mastectomy which means a decline in the level of anxiety after the administration of aromatherapy lavender flowers in patients with pre-mastectomy. The results of study are expected to be used as recommendations for health workers, especially the profession of a nurse to handle the patient's anxiety.